STRATEGI PENGEMBANGAN EKOWISATA BAHARI DI KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI, 2011 - , Rikahasnita ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to analyze the marine ecotourism development strategy and formulate a draft policy and the role of institutions in the management of ecotourism areas in the District of Sipora Utara through questionnaires and preferences of the respondents (citizens and tourists) to the ratio of 13 (thirteen) alternatives marine ecotourism development by determining priorities program development in the field of tourism. The tools used are (1) SWOT analysis to determine the position and the marine ecotourism development strategy in Sipora Utara District, (2) Analitic Hierarchy Process (AHP), a method possible decision-making that aims to determine the best choice of several options that can be selected by pairwise comparisons with respect to some criteria (economic, social and environmental sustainability) in the form of decision-making hierarchy, with the help of Expert Choice v .11.5 application program. The results using SWOT analysis shows the conditions encountered in the District of Sipora Utara marine ecotourism development is in an unfavorable position in which to face a lot of weaknesses and threats that must be overcome, then the development of marine ecotourism can use W-T Strategy (Quadrant IV) the defensive strategy, a defensive tactics directed at efforts to minimize internal weaknesses and avoiding external threats. AHP results indicate that the order of 5 (five) the best alternative in the setting of policy priorities the development of nautical tourism in the District of North Sipora viewed from economic, social and environmental sustainability, are: (1) Support the government, (2) Infrastructure, (3) Transportation and communication, (4) Transportation and community support, and (5) Safety and convenience.